Estudio de factibilidad para la creación de una empresa dedicada al diseño, fabricación y comercialización de ropa femenina en Bogotá (2021)
The objective of this work is to demonstrate the positive feasibility of creating a company dedicated to the design, manufacture and marketing of women's clothing in Bogota. This work is called feasibility study for the creation of a company dedicated to the design, manufacture and marketing of women's clothing in Bogota.